DIFFERENCES IN BLOOD GLUCOSE LEVELS AND BODY MASS INDEX AMONG FEMALE STUDENTS OF THE UNIVERSITY OF TUZLA - Belmin Bujaković; Jasmin Zahirović; Emin Mujezinović; Lejla Goletić; Nevres Muminović; Merima Aljić (Sport Scientific And Practical Aspects, 2025)
This research is aimed at the importance of the value of a healthy lifestyle, especially among the younger population (students), and as an indicator of the level of health, the optimal level of sugar in the blood and the normality of the Body Mass Index represent an established prerequisite for longer-term life and cell health. The researchers used the Mann- Whitney U test for differences between a total of 73 female students of the University of Tuzla (N-35 Faculty of Physical Education and Sport, N-38 Law). The research showed that the students of the Faculty of Physical Education and Sports who have a significantly higher number of physical activities in their daily activities have lower body mass index values and that showed a statistically significant difference between the students of these two faculties at the significance level of 99% (p<0.01 ) , also in the blood sugar level between these two groups of students, a statistically significant difference was shown at the level of 99% (p<0.01), and in this area of research, the female students of the Faculty of Physical Education and Sports have lower values (MEAN = 4.989 mmol/l) from students of the Faculty of Law (5.545 mmol/l). It is important to note that in both groups in both researched areas the results are in the normal criterion ranges, and based on the values of arithmetic averages, it can be seen that female students of the Faculty of Physical Education and Sports have lower values of blood glucose and body mass index, which would could lead to a connection with the specifics of the study programs, for example the scope of daily movement activities.